Metabolomics Analysis on Mice With Depression Ameliorated by Acupoint Catgut Embedding - Duan, Lining; Qiu, Wenhui; Bai, Guiqin; Qiao, Yiqi; Su, Shiyu; Lo, Po-Chieh; Lu, Yantong; Xu, Guofeng; Wang, Qi; Li, Min; Mo, Yousheng (Frontiers in Psychiatry, 2021)
Depression is a prevalent mental disease characterized by persistent low mood, lack of pleasure and exhaustion. Acupoint catgut embedding (ACE) is a kind of modern acupuncture treatment, which has been widely used for the treatment of a variety of neuropsychiatric diseases. To investigate the effects and underlying mechanism of ACE on depression, in this study, we applied ACE treatment at the Baihui (GV20) and Dazhui (GV14) acupoints of corticosterone (CORT)-induced depression model mice. The results showed that ACE treatment significantly attenuated the behavioral deficits of depression model mice in the open field test (OFT), elevated-plus-maze test (EPMT), tail suspension test (TST) and forced swimming test (FST). Moreover, ACE treatment reduced the serum level of adreno-cortico-tropic-hormone (ACTH), enhanced the serum levels of 5-hydroxytryptamine (5-HT) and noradrenaline (NE). Furthermore, metabolomics analysis revealed that 23 differential metabolites in the brain of depression model mice were regulated by ACE treatment for its protective effect. These findings suggested that ACE treatment ameliorated depression-related manifestations in mice with depression through the attenuation of metabolic dysfunction in brain.